An acute inflammation of the orbit simulating a metastasis in a patient with primary multiple malignant tumors - E. E. Grishina (Онкогематология)
We describe a patient with primary multiple malignant tumors who experienced exophthalmos with ophthalmoplegia during two weeks. Data of physical examination were typical for orbital malignant tumor. It was suspected a recurrence of diffuse large B-cell lymphoma with involvement of orbital tissues, so a diagnostic orbitotomy was performed. According to morphological and immunohistochemial evaluations we diagnosed acute inflammation accomplished urological infection. An active antimicrobial therapy leaded to cessation of orbital inflammation. Follow-up period was 8 months and we did not reveal inflammation recurrence.